Analisis Hubungan Beberapa Faktor dengan Pemanfaatan Pelayanan Kunjungan Ke-4 (K4) pada Ibu Hamil (Studi di Wilayah Kerja Puskesmas Kalimas, Kecamatan Randudongkal, Kabupaten Pemalang) - Novitasari, Bayu Putri; Nugroho, R. Djoko; Winarni, Sri; Mawarni, Atik (Jurnal Ilmiah Mahasiswa, 2020)
Title: Relationship of Some Factors with the Utilization of the 4th Visit Services (K4) in Pregnant Women (Study in Public Health Services of Kalimas, Randudongkal, Pemalang District).Background: In 2018 Public Health Services of Kalimas had the highest K4 achievement and had met the Minimum Service Standards (100.71%). In the implementation of K4 there are differences in the standard K4 coverage, K4 access and K4 target. This can be seen from the May 2019 standard K4 coverage of 31.24% K4 coverage of access is 35.59% and the target of 41.67%. Methods: This study aims to analyze the relationship of several factors with the use of K4 services in Public Health Services of Kalimas. This study is an explanatory research with cross sectional design. The study population numbered 112 pregnant women. By using simple sampling random technique, 93 sample were selected. Statistical test was bivariate analysis (Chi Square; Continuity Correction). Result: The result show 75.3% of mothers have low parity, 71.0% of mothers have high family income (≥UMK), 71.0% of mothers have ease in accessing accessibility, 81.7% of mothers have high decision making authority, 73.1% have support from cadres, 64.5% the availability of pregnancy information, 53.8% of mothers get incomplete services, 82.8% of mothers have never had a miscarriage, and 82.8% of mothers use K4 services with access. Conclusions: There is no relationship of parity, family income, accessibility, women’s authority in decision making, health cadre’s support, and history of miscarriage with the use of K4 services. There is relationship between the availability of pregnancy information (p-value = 0.006), completeness of service (p-value = 0.032) with the use of K4 services. Optimizing the provision of information through consoling to mothers, providing IEC (Communication, Information and Education), conducting interpersonal communication, and making regular visits to mother with help of midewives.